Negative-electrode-free lithium metal battery as well as preparation method and application thereof
By constructing the lithium plant crystal layer in situ on the negative electrode current collector of the negative electrode lithium metal battery, and combining lithium supplement additives and fluorinated amide electrolyte, the irreversible consumption of metal lithium on the current collector surface is solved, significantly extending the battery The cycle life is maintained with high energy density and low cost.
Patent Information
- Application Number
- CN202311026286.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
On the premise of maintaining the high energy density and low cost advantages of negative electrode-free lithium metal batteries, how to suppress the irreversible consumption caused by the deposition/stripping process of metal lithium on the copper current collector surface, improve the density of deposited lithium, and extend the cycle life of the battery.
Before the first charge and discharge of the battery after liquid injection packaging, an ultra-thin lithium plant crystal layer is constructed in situ on the negative electrode current collector, and an electrochemical in-situ deposition technology is used to form a dense and uniform lithium deposition layer, and combined with lithium supplementation additives and Fluorinated amide electrolyte.
It significantly improves the cycle life of negative electrode-free lithium metal batteries, while maintaining high energy density and low cost, making it easy to operate and suitable for large-scale production.
Smart Images

Figure BDA0004395667940000111 
Figure BDA0004395667940000141 
Figure HDA0004395667960000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode-free lithium metal batteries, and in particular relates to a negative electrode-free lithium metal battery with high energy density and long cycle life, and a preparation method and application thereof. Background Art
[0002] Electric vehicles and portable electronic devices are increasingly demanding lithium battery performance and cost, and are in urgent need of batteries with higher energy density and lower cost. The energy density of traditional lithium-ion batteries based on lithium-ion intercalation chemistry is approaching its limit, making it difficult to meet the development needs of various emerging fields. Lithium metal batteries have the lowest electrode potential (-3.04V vs. SHE) and the highest theoretical specific capacity (3860mAh g -1 ), which can significantly improve the energy density of batteries and has therefore been widely studied.
[0003] However, currently commercial lithium foil is generally produced by mechanical rolling with a thickness of 50-100 μm (10-20 mAh cm -2 ), the negative electrode / positive electrode capacity ratio (i.e., N / P ratio) of the lithium metal full battery constructed in this way is large, which not only affects the battery energy density, but also greatly increases the production cost due to the use of a large amount of chemically active metal lithium, and causes serious safety hazards. Therefore, practical lithium metal batteries need to use ultra-thin metal lithium foil (≤20μm) to overcome the above problems. Unfortunately, due to the viscosity of metal lithium and the unrestricted dislocation movement during extrusion deformation, the manufacture of metal lithium foil with a thickness of less than 20μm faces the challenges of poor mechanical strength and difficult production and processing. Recently, Yi Cui et al. prepared 0.5-20μm ultra-thin metal lithium foil by injecting molten lithium into a graphene oxide host (Nat.Energy 2021,6,790–798), but this type of preparation process has the problems of difficulty in mass production, low efficiency and high cost. Similarly, the preparation of ultra-thin metal lithium foil by electrochemical deposition or vacuum evaporation also has the above problems. Therefore, it is extremely challenging to produce ultra-thin lithium foil on a cheap scale, which will seriously weaken the potential commercial advantages of lithium metal batteries.
[0004] Compared with lithium metal batteries, negative electrode-free lithium metal batteries completely eliminate the active materials on the negative electrode side in the structure and only retain the current collector, which minimizes the weight and volume of the battery, maximizes the energy density of the battery, and does not involve the treatment of active metal lithium in the battery manufacturing process. While reducing production costs, it also reduces safety risks, so it has the significant advantages of high specific energy and low cost. Existing studies have shown that for zero excess lithium negative electrode-free lithium batteries, the electrodeposition / stripping behavior of limited lithium sources on the current collector is one of the key factors determining the cycle life of negative electrode-free lithium batteries. Due to its advantages such as high conductivity, high stability, easy processing and low cost, copper foil (Cu) has not been replaced as a negative electrode current collector for large-scale lithium batteries. However, the Cu current collector has an intrinsic lithium-phobic property, and lithium metal undergoes uneven nucleation and growth on the surface of the Cu current collector, causing irreversible consumption of active lithium. In order to improve the reversible and uniform deposition / stripping of lithium metal on the Cu current collector and extend the cycle life of negative electrode-free lithium metal batteries, a large amount of research work has focused on the coating modification of the current collector or the replacement of the current collector material. Liumin Suo et al. designed a liquid metal coating modified Cu current collector and combined it with a high concentration electrolyte (6MLiFSI / DME), so that the capacity retention rate of the 0.12Ah, 420Wh / kg negative electrode-free soft-pack lithium metal battery (Cu||NCM811) after 50 cycles was 84% (Adv.Energy Mater.2021,2003709). In the current collector replacement study, Hee-Tak Kim et al. reported a three-dimensional carbon current collector with a multi-vacancy defect structure, which made the button-type negative electrode-free lithium metal battery (Cu||NCM811) have a capacity retention rate of 80% after 60 cycles (Nat.Commun.2021,12,5537). However, the manufacturing process of these strategies is relatively complicated, which increases the manufacturing cost, and inevitably introduces inactive substances to reduce the energy density of the system. There is also the problem of unstable modification effect, which is not conducive to large-scale industrial production.
[0005] It can be seen that under the premise of maintaining the high energy density and low cost advantages of negative electrode-free lithium metal batteries, how to inhibit the irreversible consumption caused by the deposition / stripping process of metallic lithium on the surface of the copper current collector, improve the density of deposited lithium, and extend the cycle life of negative electrode-free lithium metal batteries is a key problem that needs to be solved urgently. Summary of the invention
[0006] The present invention utilizes in-situ crystal planting technology to construct an ultra-thin lithium crystal planting layer in-situ on the negative electrode current collector before the first charge and discharge (formation process) after the battery is filled and packaged, thereby solving the problem of uneven nucleation of metallic lithium on the negative electrode current collector. After subsequent charging, a dense and uniform lithium deposition layer with strong bonding to the current collector can be formed in-situ on the current collector, thereby significantly improving the cycle life while maintaining a high energy density; combined with a lithium supplement additive and a fluorinated amide electrolyte, the battery has a longer cycle life.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] One aspect of the present invention provides a negative electrode-free lithium metal battery.
[0009] Another aspect of the present invention provides a method for preparing the negative electrode-free lithium metal battery.
[0010] Another aspect of the present invention provides use of the negative electrode-free lithium metal battery in electronic devices, smart grids or electric vehicles.
[0011] According to one aspect of the present invention, there is provided a negative electrode-free lithium metal battery, comprising:
[0012] A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer;
[0013] Negative electrode current collector,
[0014] A lithium crystal layer formed on the surface of the negative electrode current collector corresponding to the positive electrode, wherein the lithium crystal layer is composed of metallic lithium deposited in situ by electrochemical means;
[0015] electrolyte; and
[0016] Diaphragm.
[0017] 1. Negative electrode current collector
[0018] In the present invention, the negative electrode current collector does not contain negative electrode active materials, so it is called no negative electrode.
[0019] The negative electrode current collector includes a metal current collector, such as one selected from copper, nickel, cobalt, titanium and iron or an alloy of two or more thereof, preferably copper foil; a non-metallic current collector, such as one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymer, preferably graphite paper; a metal-polymer composite current collector, such as having a three-layer structure, the middle layer is a polymer film, the upper and lower layers are metal coatings, wherein the polymer can be selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane One or more, preferably a polyimide-triphenyl phosphate copolymer with flame retardant properties. The negative electrode current collector is preferably a composite current collector of copper and polyimide-triphenyl phosphate copolymer, such as a copper-plated composite current collector of polyimide-triphenyl phosphate. The thickness of the negative electrode current collector may be 1-100 μm, preferably 1-10 μm.
[0020] The present invention also includes a coating formed on at least one side of the negative electrode current collector. The position of the coating and the lithium crystal layer is not particularly limited. The coating can be located on the lithium crystal layer, or between the negative electrode current collector and the lithium crystal layer, or form a composite layer with the lithium crystal layer. The function of the coating is to promote the dense deposition and growth of lithium metal on its surface, and / or inhibit the corrosion of the deposited lithium metal. The coating can be one of the metal-containing indium, cobalt, germanium, aluminum, tin, gold, silver, zinc, magnesium, silicon, bismuth, palladium, platinum or an alloy of two or more thereof, or can be acetylene black, ketjen black, carbon black, graphite, graphene, conductive polymer, artificial interface film (artificial SEI) containing non-metal, or a mixture of the above metal and non-metal combinations.
[0021] 2. Lithium Planting Layer
[0022] In the present invention, an ultra-thin lithium crystal layer is formed on the negative electrode current collector corresponding to the positive electrode, wherein the thickness of the lithium crystal layer is 5-2000nm, preferably 20-1000nm, and more preferably 50-500nm.
[0023] The lithium crystal planting layer of the present invention is formed by electrochemical in-situ deposition (in-situ crystal planting) of a negative electrode-free lithium metal battery, and the electrochemical in-situ deposition comprises the following steps:
[0024] The negative electrode-free lithium metal battery is charged with constant current and / or constant voltage after liquid injection and packaging and before formation. The nucleation overpotential of the metal lithium (relative to the standard potential of the metal lithium) is controlled to be 0.1-2V, preferably 0.6-1.5V, especially 1V during the charging process.
[0025] In some embodiments, the constant current charging process is: at temperature T 1At a constant charge rate C 1 Charging, charging time is t 1 ;
[0026] The constant voltage charging process is: at temperature T 2 At a constant charging voltage V 1 Charging, charging capacity is R 1 .
[0027] Among them, C 1 0.3 to 10.0°C, preferably 0.5 to 5°C, more preferably 0.8 to 3°C, particularly 1°C,
[0028] t 1 0.1 to 3600 s, preferably 1 to 100 s, more preferably 10 to 60 s, particularly 36 s,
[0029] T 1 The temperature is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, and particularly 0°C.
[0030] V 1 3.2 to 6 V, preferably 3.8 to 5 V, more preferably 3.8 to 4.2 V, particularly 4.2 V,
[0031] R 1 0.01~1mAh / cm 2 , preferably 0.02 to 0.5 mAh / cm 2 , more preferably 0.02 to 0.2 mAh / cm 2 , especially 0.056 mAh / cm 2 ,
[0032] T 2 It is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, particularly 25°C.
[0033] The negative electrode-free lithium metal battery is charged to electrochemically deposit metallic lithium in situ on the negative electrode current collector to form a lithium planting layer. The parameter selection of constant current charging and / or constant voltage charging is to regulate the nucleation overpotential (P) of metallic lithium on the negative electrode current collector, wherein P is 0.1 to 2 V relative to the standard potential of metallic lithium to obtain a lithium planting layer with high coverage. The present invention can deposit (charge) a capacity of 0.02 to 0.2 mAh / cm at a relatively low deposition (charging) capacity of 0.02 to 0.2 mAh / cm 2 Under the condition of high coverage, it is preferred that the ratio (coverage) of metal lithium (thinner lithium core) covering the surface of the negative electrode current collector is >80%, further >90%, or even close to 100%. The calculation formula of this ratio (coverage) is as follows:
[0034] The ratio of metal lithium covering the negative electrode current collector surface % = S 1 / S×100%, where S is the area of the negative electrode collector, S 1 is the projected area of metallic lithium deposited within area S on the negative electrode current collector.
[0035] The lithium crystal layer formed by the in-situ crystal planting method can achieve close bonding with the negative electrode current collector, improve the compactness of metal lithium deposition in the subsequent charge and discharge process, and extend the cycle life of the negative electrode-free lithium metal battery. After the battery has been cycled for a long period of time, a lithium deposition layer is formed on the lithium crystal layer, which has a strong bonding with the current collector.
[0036] The in-situ crystal planting process described in the present invention is different from the conventional lithium-ion battery formation. Conventional formation optimizes the charge and discharge parameters to regulate the electrolyte-electrode interface reaction to obtain a high-quality solid electrolyte interface film (SEI / CEI) and discharge the gas products generated by the electrolyte-electrode interface reaction.
[0037] In practical applications, the in-situ crystal planting process can be combined with the formation step without a time interval, but the in-situ crystal planting process is still performed before the formation step.
[0038] 3. Positive electrode
[0039] In the present invention, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector.
[0040] There is no particular limitation on the positive electrode current collector, which can be a positive electrode current collector conventionally used for lithium batteries, including a metal current collector, such as one selected from aluminum, titanium, nickel and iron or an alloy thereof, preferably aluminum foil; a non-metallic current collector, such as one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymers, preferably carbon fiber paper; a metal-polymer composite current collector, such as having a three-layer structure, the middle layer is a polymer film, and the upper and lower layers are metal coatings, wherein the polymer can be one or more of polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a polyimide-triphenyl phosphate copolymer with flame retardant properties. The positive electrode current collector is preferably a composite current collector of aluminum and polyimide-triphenyl phosphate copolymer, such as an aluminum-plated composite current collector of polyimide-triphenyl phosphate copolymer. The composite current collector can effectively enhance the safety performance of the battery, reduce the cost of raw materials, and increase the energy density of the battery. The thickness of the positive electrode current collector can be 1-100 μm, preferably 1-20 μm.
[0041] The positive electrode active material layer of the present invention comprises a positive electrode active material and a lithium supplement additive. In addition, the positive electrode active material layer may also comprise: a conductive material for enabling electrons to move smoothly in the positive electrode, a binder for increasing the bonding force between the positive electrode active materials or between the positive electrode active material and the positive electrode current collector, the positive electrode active material and the lithium supplement additive.
[0042] There is no particular limitation on the positive electrode active material, and it can be a positive electrode active material conventionally used in lithium batteries, including ternary nickel cobalt manganese oxide positive electrode materials, such as Li[Ni 0.5 Mn 0.2 Co 0.3 ]O 2 (NCM523), Li[Ni 0.6 Mn 0.2 Co 0.2 ]O 2 (NCM622), Li[Ni 0.8 Mn 0.1 Co 0.1 ]O 2 (NCM811), Li[Ni 0.9 Mn 0.05 Co 0.05 ]O 2 (NCM955), lithium-rich manganese-based positive electrode material (LMR), lithium nickel manganese oxygen positive electrode material (LNMO), lithium iron phosphate positive electrode material (LiFePO 4 ), lithium manganese oxide positive electrode material (LiMn 2 O 4 ), lithium manganese iron phosphate positive electrode material (LMFP), lithium cobalt oxide positive electrode material (LiCoO 2 ), lithium sulfide positive electrode material (Li 2 S) one or more, but not limited thereto. Preferably, the positive electrode adopts ternary nickel cobalt lithium manganese oxide positive electrode materials (NCM523, NCM622, NCM811, NCM955) with different nickel contents, especially NCM811.
[0043] Based on the total weight of the positive electrode active material layer, the positive electrode active material may be contained in an amount of 80 wt % to 99 wt %. If the amount of the positive electrode active material is less than the range, the energy density of the battery will be reduced. If the amount of the positive electrode active material exceeds the range, the content of the lithium supplement additive is too small, resulting in an insignificant effect on the improvement of the battery cycle life.
[0044] The lithium supplement additive is a lithium-containing compound with the ability to release lithium ions and an irreversible capacity of >50%, including binary lithium-containing compounds, such as Li 2 O, Li 2 O 2 , Li3 N, Li 2 S, Li 2 C 2 O 4 etc., preferably Li 2 C 2 O 4 ; Li-rich compounds, such as Li 2 Ni 1-x M x O 2 (wherein 0≤x<1, and M is at least one selected from Mn, Fe, Co, Cu, Zn, Mg, Cd), Li 5 Fe 1- x N x O 4 (wherein 0≤x<1, and N is at least one selected from Mn, Ni, Co, Cu, Zn, Mg, Cd), etc., preferably the lithium supplement additive is Li 2 NiO 2 and Li 5 FeO 4 One or both of the following.
[0045] Based on the total weight of the positive electrode active material layer, the lithium supplement additive may be contained in an amount of 0.5 wt % to 20 wt %, preferably 2 wt % to 10 wt %. Similarly, if the amount of the lithium supplement additive is less than the range, the effect of improving the battery cycle life will not be obvious. If the amount of the lithium supplement additive exceeds the range, not only the energy density will be compromised, but other battery properties may also deteriorate, such as cycle life, power, safety performance, etc.
[0046] In addition, the conductive material can be a carbon material such as carbon black, acetylene black, Ketjen black, carbon nanotubes; or a conductive polymer such as polyaniline, polythiophene, polyacetylene and polypyrrole. Based on the total weight of the positive electrode active material layer, the conductive material can be contained in an amount of 0.1 wt% to 5 wt%.
[0047] In addition, the binder may be polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, polymethyl methacrylate, polyvinylidene fluoride, polyhexafluoropropylene and a copolymer of polyvinylidene fluoride (product name: Kynar), polyethyl acrylate, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polystyrene and derivatives, blends and copolymers thereof. Based on the total weight of the positive electrode active material layer, the binder may preferably be contained in an amount of 0.1 wt % to 5 wt %.
[0048] 4. Electrolyte
[0049] In the present invention, the electrolyte contains at least one lithium salt and an organic solvent. In addition, the electrolyte may further contain functional additives (i.e., electrolyte additives) and / or flame retardants or inert diluents as needed, thereby reducing the flammability or cost of the electrolyte.
[0050] There is no particular restriction on the choice of electrolyte, and conventional electrolytes for negative electrode-free lithium metal batteries can be selected, such as local high-concentration electrolytes, high-concentration electrolytes, weakly solvated electrolytes, and the like.
[0051] In some embodiments, the electrolyte comprises at least one boron-containing lithium salt and a fluorinated amide compound, wherein the electrolyte uses the boron-containing lithium salt as a main salt and the fluorinated amide compound as an organic solvent.
[0052] The boron-containing lithium salt can be one or more selected from lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium fluoroalkoxyborate, lithium fluoroalkoxyfluoroborate, lithium fluoroalkoxybisfluoroborate, and lithium fluoroalkoxytrifluoroborate, preferably lithium difluorooxalatoborate (LiDFOB).
[0053] The fluorinated amide compound can be one or more selected from N,N-dimethyltrifluoroacetamide, N-methoxy-N-methyltrifluoroacetamide, N-methyltrifluoroacetamide, N,N-diethyltrifluoroacetamide, N-(trifluoromethanesulfonyl)trifluoroacetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, bis(trimethylsilyl)trifluoroacetamide, N-methyltrimethylsilyltrifluoroacetamide, N-methylbis(trifluoroacetyl)amide, trifluoroacetamide, and bistrifluoroacetamide, preferably N,N-dimethyltrifluoroacetamide.
[0054] Based on the total weight of the electrolyte, it can contain 5 wt% to 50 wt% (e.g., 10 wt% to 35 wt%) of boron-containing lithium salt. If the content of lithium salt is less than 5 wt%, the ionic conductivity of the electrolyte will be reduced, affecting the deposition effect of metallic lithium. If the content of lithium salt exceeds 50 wt%, the cost and viscosity of the electrolyte will be increased, and the wettability to the electrode and the diaphragm will be reduced.
[0055] In some embodiments, the electrolyte comprises lithium difluorooxalatoborate (LiDFOB) and N,N-dimethyltrifluoroacetamide, and the molar ratio of lithium difluorooxalatoborate (LiDFOB) to N,N-dimethyltrifluoroacetamide is 1:5.
[0056] The functional additive may be an additive conventionally used in lithium battery electrolytes in the art, for example, a salt or an organic solvent, such as selected from tris(2,2,2-trifluoroethyl)phosphite (TTFEP), 1,3,6-hexanetrinitrile (HTCN), tris(trimethylsilyl)borate (TMSB), tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)phosphite (TMSPi), hexamethyldisilazane (HMDS), 1,3-propylene sultone (PRS), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), di(2,2,2-trifluoroethyl) carbonate (TFEC), fluoroethyl methyl carbonate (FEMC), vinylene carbonate (VC), propylene sulfite (PS), trifluoromethylethylene carbonate (TFPC), vinyl sulfate (DTD), vinyl sulfite (ES), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalatophosphate) (LiDODFP), lithium tetrafluorooxalatophosphate (LiTFOP), lithium nitrate (LiNO 3 ), lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), one or more of lithium trifluoromethanesulfonate (LiOTf), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0057] The functional additives can be added by those skilled in the art according to the desired functions and the appropriate amount can be determined. For example, based on the total weight of the electrolyte, the functional additives can be contained in an amount of 0.1 wt % to 10 wt %, preferably 0.5 wt % to 5 wt %.
[0058] The flame retardant or inert diluent may be a flame retardant or inert diluent conventionally used in the art for lithium battery electrolytes, for example, it may be selected from any one or more of halogenated ethers, halogenated esters, hydrocarbons, halogenated hydrocarbons, aromatic compounds, nitrogen-containing compounds and their derivatives, such as 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,3,3,3-hexafluoropropyl methyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, 1,2-bis(1,1,2,2-tetrafluoro The invention also includes but is not limited to 1,2-difluoro-1,2-difluoro-2-(1,1,2,2-tetrafluoroethoxy) ... Preferably, the flame retardant or inert diluent is selected from 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl nonafluorobutyl ether, and m-fluorotoluene.
[0059] The flame retardant or inert diluent can be added by a person skilled in the art according to the desired function and the appropriate amount can be determined. For example, based on the total amount of the electrolyte, the flame retardant or inert diluent can be contained in an amount of 5 wt % to 90 wt %, preferably 20 wt % to 50 wt %.
[0060] 5. Diaphragm
[0061] In the present invention, the diaphragm is a physical diaphragm having the function of physically separating electrodes, and can be used without particular restriction, as long as it is used as a diaphragm in a conventional lithium secondary battery, and in particular, a diaphragm having low resistance to ion migration in an electrolyte and having excellent electrolyte impregnation ability is preferred. Specifically, the diaphragm can be a porous polymer film, for example, a porous polymer film made of one of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a composite porous polymer film made of two or more, which can be used alone or in the form of a laminate, or can be a porous non-woven fabric, for example, a non-woven fabric made of glass fiber with a high melting point, polyethylene terephthalate fiber, etc. The diaphragm can contain a surface functional coating material, such as a ceramic coating, a solid electrolyte coating, or a composite coating of two or more, but is not limited thereto. The ceramic may include: aluminum oxide (Al 2 O 3 ), magnesium oxide (MgO), titanium dioxide (TiO 2 )、ZrO 2 ), silicon dioxide (SiO 2 ), barium titanate (BaTiO 3 ) etc.; the solid electrolyte may include: lithium phosphorus oxynitride (LiPON), lithium zinc germanate (LISICON), lithium germanium phosphosulfur (LGPS), lithium phosphorus sulfur chlorine (LPSCl), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAG P), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), halide solid electrolyte (Li x MCl 6 , M is a metal element), polyethylene oxide (PEO), polysiloxane (PS), polypropylene carbonate (PPC), polyacrylonitrile (PAN), polyacrylate (PBA), polymethyl methacrylate (PMMA) and polyvinylidene fluoride (PVDF), etc.
[0062] In addition to the positive electrode, negative electrode, separator and electrolyte mentioned above, the battery of the present invention may also include other structures such as a chip, a capacitor, a casing and the like as required.
[0063] The anode-free lithium metal battery according to the present invention is a cathode-free lithium metal battery with high energy density and long cycle life. Here, "high energy density and long cycle life" means that the cathode-free lithium metal battery according to the present invention further significantly improves its cycle life while maintaining or maintaining the high energy density (>350Wh / kg, even >400Wh / kg, >450Wh / kg and >500Wh / kg) of conventional cathode-free lithium metal batteries.
[0064] According to another aspect of the present invention, a method for preparing the negative electrode-free lithium metal battery is provided, comprising the following steps:
[0065] Assembling a positive electrode, a negative electrode current collector, a separator and an electrolyte into a negative electrode-free lithium metal battery;
[0066] The negative electrode-free lithium metal battery is subjected to constant current charging and / or constant voltage charging after liquid injection and packaging and before formation, and the nucleation overpotential of the metal lithium (relative to the standard potential of the metal lithium) is controlled to be 0.1-2V, preferably 0.6-1.5V during the charging process, to obtain the negative electrode current collector including the formation of the lithium planting layer.
[0067] In some embodiments, the constant current charging process is: at temperature T 1 At a constant charge rate C 1 Charging, charging time is t 1 ;
[0068] The constant voltage charging process is: at temperature T 2 At a constant charging voltage V 1 Charging, charging capacity is R 1 .
[0069] Among them, C 1 0.3 to 10.0°C, preferably 0.5 to 5°C, more preferably 0.8 to 3°C, particularly 1°C,
[0070] t 1 0.1 to 3600 s, preferably 1 to 100 s, more preferably 10 to 60 s, particularly 36 s,
[0071] T 1 The temperature is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, and particularly 0°C.
[0072] V 1 3.2 to 6 V, preferably 3.8 to 5 V, more preferably 3.8 to 4.2 V, particularly 4.2 V,
[0073] R 1 0.01~1mAh / cm 2 , preferably 0.02 to 0.5 mAh / cm 2 , more preferably 0.02 to 0.2 mAh / cm 2 , especially 0.056 mAh / cm 2 ,
[0074] T 2 It is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, particularly 25°C.
[0075] The positive electrode can be prepared according to a conventional method, and specifically, a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a lithium supplement additive, a conductive material and a binder in an organic solvent or water is coated on a positive electrode current collector, followed by drying and optionally rolling. In this case, the organic solvent can evenly disperse the positive electrode active material, the lithium supplement additive, the binder and the conductive material, and can be easily evaporated. Specifically, N-methylpyrrolidone, dimethylformamide, ethylene glycol dimethyl ether, acetonitrile, etc. can be used as an organic solvent.
[0076] According to another aspect of the present invention, there is provided use of the negative electrode-free lithium metal battery in electronic devices, smart grids or electric vehicles.
[0077] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".
[0078] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.
[0079] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0080] In this document, under the premise of achieving the purpose of the invention, numerical values should be understood to have the accuracy of the number of significant digits of the numerical value. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.
[0081] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
[0082] Beneficial Effects
[0083] (1) The present invention electrochemically forms a dense ultra-thin lithium phytocrystalline layer composed of metallic lithium in situ on the negative electrode current collector, obtains more physical contact surfaces with the current collector, and induces the high-quality growth of the lithium deposition layer formed by subsequent conventional charging, and forms a close contact with the substrate. Without affecting the energy density and cost, the cycle stability of the negative electrode-free lithium metal battery can be significantly improved. Further combined with lithium supplement additives and fluorinated amide electrolytes, the effect can be made more significant;
[0084] (2) The in-situ crystal planting method provided by the present invention does not reduce energy density, does not increase cost, is easy to operate, and is suitable for large-scale production and application; it has wide adaptability to various electrolytes; it is sustainable, and even after the battery has been cycled many times, the lithium crystals formed by the in-situ crystal planting can still remain on the surface of the current collector;
[0085] (3) The present invention combines an in-situ formed lithium-planted crystal layer, a lithium supplement additive, and a fluorinated amide electrolyte with a negative electrode-free lithium metal battery system. In actual test conditions, the energy density is 533 Wh kg -1 The cycle life of the Cu||NCM811 anode-free soft-pack lithium metal battery (100% DoD) reaches 232 times; the energy density is 426Wh kg -1 The cycle life of the Cu||NCM811 negative electrode-free soft-pack lithium metal battery (80% DoD) reaches 725 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1The lithium||copper button battery assembled in Comparative Example 1 and Example 1 shows the state of the lithium deposition layer on the Cu foil after being bent after 10 cycles, wherein (a) is the bending state of Comparative Example 1, and (b) is the bending state of Example 1.
[0087] Figure 2 The SEM morphology of the lithium deposition layer near the Cu foil side of the lithium||copper button-type batteries assembled in Comparative Example 1 and Example 1 after 10 cycles (bottom view of the lithium deposition layer), wherein (a) is the SEM morphology of the lithium deposition layer near the Cu foil side of Comparative Example 1, and (b) is the SEM morphology of the lithium deposition layer near the Cu foil side of Example 1.
[0088] Figure 3 The images of the lithium crystal layer formed in situ on the current collector of the negative electrode-free soft-pack lithium metal battery assembled in Example 2 after in-situ crystal planting treatment and the lithium crystal layer on the current collector after 10 cycles are shown, where (a) is the image of the lithium crystal layer after the in-situ crystal planting treatment, and (b) is the image of the lithium crystal layer after 10 cycles.
[0089] Figure 4 The time-voltage curves corresponding to the in-situ crystal planting process of the negative electrode-free soft-pack lithium metal batteries assembled in Example 2, Example 3, Example 4, Example 5 and Comparative Example 2 are shown.
[0090] Figure 5 An image showing the lithium crystal layer on the current collector after in-situ crystal planting treatment of the negative electrode-free soft-pack lithium metal batteries assembled in Example 2, Example 3, Example 4 and Example 5. DETAILED DESCRIPTION
[0091] The present invention will be described in detail below according to the accompanying drawings and preferred embodiments, and the purpose and effect of the present invention will become more clear. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0092] Preparation Example:
[0093] Preparation of lithium||copper (Li||Cu) button battery:
[0094] In a glove box filled with argon, the positive electrode shell, working electrode (copper foil), diaphragm, electrolyte, counter electrode (metal lithium sheet), gasket, spring and negative electrode shell are assembled in this order. Then, the button battery is placed with the negative electrode side facing up on the button battery sealing machine mold and pressed to complete the preparation of the lithium||copper button battery.
[0095] The counter electrode and reference electrode were 200 μm thick lithium metal sheets purchased from Zhongneng Lithium Industry;
[0096] The working electrode was 20 μm thick copper foil purchased from Shenzhen Kejing;
[0097] The separator was a 12 μm thick polyethylene (PE) separator purchased from Celgard.
[0098] Preparation of negative electrode-free soft-pack lithium metal battery:
[0099] The assembly is carried out in the order of lamination, tab welding, top and side sealing, liquid injection and packaging. The liquid injection and packaging are carried out in a glove box and a vacuum pre-sealing machine is used for packaging.
[0100] Preparation of positive electrode sheet: Make positive electrode active material, lithium supplement additive, binder and conductive agent into slurry, coat both sides on 4μm thick aluminum foil, and cut to size.
[0101] The negative electrode current collector was 4 μm thick copper foil purchased from Shenzhen Kejing;
[0102] The separator was a 12 μm thick polyethylene (PE) separator purchased from Celgard;
[0103] Aluminum tabs, nickel tabs and 113 μm thick aluminum-plastic film were purchased from Shenzhen Kejing.
[0104] Preparation of electrolyte:
[0105] The local high concentration electrolyte is prepared from lithium bis(fluorosulfonyl)imide (LiFSI) with a molar ratio of 1.0:1.2:3.0:ethylene glycol dimethyl ether (DME):1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE). Specifically, 1.50g of lithium bis(fluorosulfonyl)imide (LiFSI) is dissolved in 1.0mL of ethylene glycol dimethyl ether (DME) solvent to obtain a high concentration electrolyte. Then, 1.0mL of the high concentration electrolyte is mixed with 1.93mL of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) solvent to obtain a local high concentration electrolyte, in which the mass proportion of lithium salt is 19.0wt%. This local high concentration electrolyte is the local high concentration electrolyte with the best performance reported so far.
[0106] The fluorinated amide electrolyte is prepared from lithium difluorooxalate borate (LiDFOB) and N,N-dimethyltrifluoroacetamide in a molar ratio of 1:5. Specifically, 0.25 g of lithium difluorooxalate borate (LiDFOB) is dissolved in 1.0 mL of N,N-dimethyltrifluoroacetamide solvent to obtain a fluorinated amide electrolyte, in which the mass proportion of lithium salt is 17.2 wt%.
[0107] Constant current charge and discharge test of non-negative electrode soft-pack lithium metal battery: The test was conducted with the Xinwei battery test system at a constant current within the set voltage range, where 1C = 5.6 mA cm -2The cycle life of the battery is defined as 80% capacity retention based on the initial discharge capacity at 0.2C.
[0108] Test method for the ratio (coverage) of metal lithium covering the surface of the negative electrode current collector:
[0109] After the negative electrode current collector after in-situ crystal planting was photographed by scanning electron microscope, 5 groups of 2×2μm test areas were randomly selected and the total projected area of all metal lithium on the current collector in the 5 groups of test areas was measured (A, μm 2 ), and calculate the average value (average coverage) of the 5 groups of data according to the following formula.
[0110]
[0111] Example 1: Lithium||Copper (Li||Cu) Button Cell
[0112] Metallic lithium was selected as the counter electrode and reference electrode, copper foil was used as the working electrode, and polyethylene (PE) was used as the diaphragm. 70 μL of local high-concentration electrolyte was injected into the button cell in an argon-filled glove box. In-situ crystal planting was performed before the first charge and discharge cycle: at 0°C, 5 mA cm -2 The battery was discharged at a current density of 1.500 Å for 36 s, and a lithium-planted crystal layer was formed on the copper foil current collector.
[0113] Comparative Example 1: Lithium||Copper (Li||Cu) Button Cell
[0114] The difference between the comparative example and the embodiment 1 is that the in-situ crystal planting process before the first charge and discharge cycle is eliminated.
[0115] The batteries obtained in Comparative Example 1 and Example 1 were respectively subjected to the following operations:
[0116] First, 0.1 mA cm -2 The current density of the electrodeposition on copper foil is 5 mAh cm -2 of metallic lithium, then at 0.5 mA cm -2 ,3mAh cm -2 After 10 stripping / deposition cycles under the conditions of , the 10th battery sample was collected and the morphology of the Cu foil lithium deposition layer was observed after disassembly.
[0117] Figure 1(a) and (b) show the morphology of the lithium deposited layer of the Cu foil observed using a scanning electron microscope (SEM) after the batteries of Comparative Example 1 and Example 1 were disassembled after 10 cycles. After bending, it was found that the lithium deposited layer (thickness 50.3 μm) on the Cu foil without in-situ crystal planting treatment (Comparative Example 1) immediately broke and fell off the current collector after only one small-angle bending; while the lithium deposited layer (thickness 32.7 μm) on the Cu foil with in-situ crystal planting treatment (Example 1) at 0°C did not break even after multiple higher-degree bendings, and still showed a tight contact with the Cu foil.
[0118] The lithium deposited layer on the Cu foil is peeled off. For the lithium deposited layer of Comparative Example 1, since the contact with the current collector is very weak, the lithium deposited layer can be peeled off only by bending the current collector at a small angle. For Example 1, since the contact between the lithium deposited layer and the current collector is very close, it is necessary to use double-sided conductive copper tape to stick on the lithium deposited layer for peeling, and the above lithium deposited layer is pasted on the SEM sample stage for morphology observation.
[0119] Figure 2 (a) and (b) show the SEM morphology of the lithium deposition layer near the Cu foil side after the lithium deposition layer of Comparative Example 1 and Example 1 is peeled off (bottom view of the lithium deposition layer). It can be seen from the figure that the bottom view of the lithium deposition layer without in-situ crystal planting treatment (Comparative Example 1) shows more moss and dendrite-like lithium, while the bottom view of the lithium deposition layer with in-situ crystal planting treatment at 0°C (Example 1) observed a significantly suppressed high aspect ratio lithium deposition morphology, and the densely stacked granular deposited lithium showed more mutual contact.
[0120] Example 2: Negative-electrode-free soft-pack lithium metal battery
[0121] The positive electrode is a 4 μm thick aluminum foil coated on both sides with high nickel ternary positive electrode nickel cobalt manganese oxide Li[Ni 0.8 Mn 0.1 Co 0.1 ]O 2 (NCM 811) positive electrode material layer, composed of 97.5wt.% active material, 1.0wt.% conductive agent, 1.5wt.% binder, single-sided coating density is 26.5mg / cm 2 ; The negative electrode is a 4μm thick copper foil current collector with no active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and a vacuum pre-sealer is used for packaging. The electrolyte adopts a local high-concentration electrolyte, in which the mass proportion of lithium salt is 19.0wt%. The electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.7Ah, and the corresponding energy density is 549Wh / kg.
[0122] In-situ crystal planting treatment: In-situ crystal planting treatment is carried out after the battery is filled and packaged but before formation: at a temperature of 0°C, at a constant charge rate of 1C = 5.6mAcm -2 Charging, the charging time is 36s, and a lithium crystal layer is formed on the surface of the copper foil. Figure 3 As shown in (a), lithium is evenly distributed and has a size of ~100 nm.
[0123] Electrochemical test method: Perform conventional charge and discharge cycles: at a temperature of 25°C, the voltage range is set at 2.8-4.4V (100% DoD), and after cycles at a charge and discharge rate of 0.1C, perform long-term charge and discharge cycles at a charge rate of 0.2C and a discharge rate of 0.5C.
[0124] Figure 3 (b) shows the image of the planted crystal layer still maintained on the surface of the current collector after 10 cycles. The morphology of the planted crystal layer has not changed significantly, indicating that it has sustainable characteristics.
[0125] Embodiment 3:
[0126] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and Example 2 is that the temperature of the in-situ crystal planting treatment is set to 20°C.
[0127] Embodiment 4:
[0128] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and Example 2 is that the temperature of the in-situ crystal planting treatment is set to 40°C.
[0129] Embodiment 5:
[0130] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and Example 2 is that the temperature of the in-situ crystal planting treatment is set to 60°C.
[0131] Embodiment 6:
[0132] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and that of Example 2 is that the electrolyte uses a fluorinated amide electrolyte with a molar ratio of 1:5.
[0133] Embodiment 7:
[0134] The positive electrode is a 4 μm thick aluminum foil coated on both sides with high nickel ternary positive electrode nickel cobalt manganese oxide Li[Ni 0.8 Mn 0.1 Co 0.1 ]O 2 (NCM811) positive electrode material layer, composed of 90.0wt.% NCM811, 7.5wt.% Li 2 NiO 2Active material, 1.0wt.% conductive agent, 1.5wt.% binder, single-sided coating density is 26.5mg / cm 2 The negative electrode is a 4μm thick copper foil current collector without active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and a vacuum pre-sealing machine is used for packaging. The electrolyte uses a local high-concentration electrolyte, and the electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.62Ah, and the corresponding energy density is 533Wh / kg.
[0135] In-situ crystal planting: at 0°C, with a constant charge rate of 1C = 5.6 mA cm -2 Charging, charging time is 36s.
[0136] The electrochemical test method is the same as that in Example 2.
[0137] Embodiment 8:
[0138] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and Example 7 is that the electrolyte uses a fluorinated amide electrolyte with a molar ratio of 1:5.
[0139] The electrochemical test method is the same as that in Example 2.
[0140] Embodiment 9:
[0141] The preparation method of the negative electrode-free soft-pack lithium metal battery is the same as that in Example 8.
[0142] The electrochemical test method is the same as that of Example 2, except that the voltage range is set at 3.6-4.3 V (80% DoD).
[0143] Comparative Example 2:
[0144] The difference between the preparation method of the negative electrode-free soft-pack lithium metal battery and Example 2 is that the in-situ crystal planting process is eliminated.
[0145] Comparative Example 3:
[0146] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Example 7 in that the in-situ crystal planting process is eliminated.
[0147] Comparative Example 4:
[0148] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Example 2 in that the electrolyte uses a fluorinated amide electrolyte with a molar ratio of 1:5 and the in-situ crystal planting process is cancelled.
[0149] Comparative Example 5:
[0150] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Example 7 in that the electrolyte uses a fluorinated amide electrolyte with a molar ratio of 1:5 and the in-situ crystal planting process is cancelled.
[0151] Table 1 summarizes the test results of Examples 2-9 and Comparative Examples 2-5.
[0152] Table 1
[0153]
[0154] It can be seen from Table 1 that in the negative electrode-free soft-pack lithium metal battery with a local high-concentration electrolyte, after the in-situ crystal planting treatment is implemented (Example 2), the cycle life can be increased by 65.8% compared with that of Comparative Example 2; in the negative electrode-free soft-pack lithium metal battery with a fluorinated amide electrolyte, after the in-situ crystal planting treatment is implemented (Example 6), the cycle life can be increased by 45.7% compared with that of Comparative Example 4, indicating that the in-situ crystal planting treatment can increase the cycle life of the battery in both of the above electrolytes.
[0155] After adding lithium supplement additives to the negative electrode-free soft-pack lithium metal battery with local high concentration electrolyte and combining with in-situ crystal planting treatment (Example 7), the cycle life can be increased by 97.4% compared with Comparative Example 2; after adding lithium supplement additives to the negative electrode-free soft-pack lithium metal battery with fluorinated amide electrolyte and combining with in-situ crystal planting treatment (Example 8), the cycle life is increased by 186.5% compared with Comparative Example 4. Further controlling the discharge depth to 80% (Example 9), the cycle life can be increased by 9 times compared with Comparative Example 4. This result shows that the synergistic effect of in-situ crystal planting treatment, fluorinated amide electrolyte and lithium supplement additive can significantly extend the cycle life of the battery while maintaining the high energy density characteristics of the negative electrode-free soft-pack lithium metal battery.
[0156] Figure 4 The time-voltage curve of the in-situ crystal planting process of the negative electrode-free soft-pack lithium metal battery after the battery is filled and packaged before formation. The rate of the in-situ crystal planting process is 1C rate (1C = 5.6 mA cm -2 ), and then undergoes a 36 s fast charge, during which the capacity of the plated lithium metal is very low (~0.056 mAh cm -2 ), so it will not affect the energy density of the soft-pack battery.
[0157] Figure 5 The morphology of the crystal layer on the current collector of the negative electrode-free soft-pack lithium metal battery after the in-situ crystal treatment before the battery is formed after the battery is filled and packaged. Among them, the in-situ crystal temperature (0°C) of Example 2 makes the average coverage of the metal lithium on the current collector reach 95%, basically achieving uniform and dense coverage of the metal lithium on the current collector.
Claims
1. A negative electrode-free lithium metal battery, comprising: A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer; Negative electrode current collector, A lithium crystal layer formed on the surface of the negative electrode current collector corresponding to the positive electrode, wherein the lithium crystal layer is composed of metallic lithium deposited in situ by electrochemical means; electrolyte; and Diaphragm.
2. The negative electrode-free lithium metal battery according to claim 1, wherein: The thickness of the lithium planting layer is 5-2000nm, preferably 20-1000nm, and more preferably 50-500nm.
3. The negative electrode-free lithium metal battery according to claim 1, wherein: The electrochemical in-situ deposition comprises the following steps: The negative electrode-free lithium metal battery is charged with constant current and / or constant voltage after liquid injection and packaging and before formation. During the charging process, the nucleation overpotential of the metal lithium is controlled to be 0.1-2V relative to the standard potential of the metal lithium, preferably 0.6-1.5V; Preferably, the constant current charging process is: charging at a constant charging rate C1 at a temperature T1, and the charging time is t1; The constant voltage charging process is: at temperature T2, charging with a constant charging voltage V1 and a charging capacity of R1; Among them, C1 is 0.3 to 10.0C, preferably 0.5 to 5C, more preferably 0.8 to 3C, t1 is 0.1 to 3600 s, preferably 1 to 100 s, more preferably 10 to 60 s, T1 is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, V1 is 3.2 to 6 V, preferably 3.8 to 5 V, more preferably 3.8 to 4.2 V, R1 is 0.01~1mAh / cm 2 , preferably 0.02 to 0.5 mAh / cm 2 , more preferably 0.02 to 0.2 mAh / cm 2 , T2 is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C; Preferably, the ratio of the metal lithium covering the surface of the negative electrode current collector is greater than 80%.
4. The negative electrode-free lithium metal battery according to claim 1, wherein: The negative electrode current collector is selected from a metal current collector, a non-metal current collector or a metal-polymer composite current collector; Preferably, the metal current collector is an alloy of one or more selected from copper, nickel, cobalt, titanium and iron, preferably copper foil; the non-metallic current collector is one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymer, preferably graphite paper; the polymer in the metal-polymer composite current collector is one or more selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a composite current collector of copper and polyimide-triphenyl phosphate copolymer; Preferably, the negative electrode-free lithium metal battery further comprises a coating formed on at least one side of the negative electrode current collector, wherein the coating is selected from a metal coating, a non-metal coating or a metal-non-metal mixed coating; Preferably, the metal is one selected from indium, cobalt, germanium, aluminum, tin, gold, silver, zinc, magnesium, silicon, bismuth, palladium and platinum, or an alloy of two or more of the foregoing, and the non-metal is one or more selected from acetylene black, ketjen black, carbon black, graphite, graphene, conductive polymers and artificial interface films.
5. The negative electrode-free lithium metal battery according to claim 1, wherein: The positive electrode current collector is selected from a metal current collector, a non-metal current collector or a metal-polymer composite current collector; Preferably, the metal current collector is an alloy of one or more selected from aluminum, titanium, nickel and iron, preferably aluminum foil; the non-metallic current collector is one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymer, preferably carbon fiber paper; the polymer in the metal-polymer composite current collector is one or more selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a composite current collector of aluminum and polyimide-triphenyl phosphate copolymer.
6. The negative electrode-free lithium metal battery according to claim 1, wherein: The positive electrode active material layer comprises a positive electrode active material and a lithium supplement additive; Preferably, the positive electrode active material is one or more selected from the group consisting of a ternary nickel cobalt lithium manganese oxide positive electrode material, a lithium-rich manganese-based positive electrode material, a lithium nickel manganese oxygen positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganese oxide positive electrode material, a lithium iron manganese phosphate positive electrode material, a lithium cobalt oxide positive electrode material and a lithium sulfide positive electrode material, preferably a ternary nickel cobalt lithium manganese oxide positive electrode material; Preferably, the lithium-supplementing additive is one or more selected from binary lithium-containing compounds and lithium-rich compounds; the binary lithium-containing compound is one or more selected from Li2O, Li2O2, Li3N, Li2S and Li2C2O4, preferably Li2C2O4; the lithium-rich compound is one or more selected from Li2Ni 1-x M x O2 or Li5Fe 1-x N x O4, wherein 0≤x<1, and M is at least one selected from Mn, Fe, Co, Cu, Zn, Mg, and Cd, and N is at least one selected from Mn, Ni, Co, Cu, Zn, Mg, and Cd. Preferably, the lithium supplement additive is one or both of Li2NiO2 and Li5FeO4.
7. The negative electrode-free lithium metal battery according to claim 1, wherein: The electrolyte comprises at least one lithium salt and an organic solvent, and preferably, the electrolyte further comprises a flame retardant or an inert diluent; Preferably, the electrolyte comprises at least one boron-containing lithium salt, and a fluorinated amide compound; The boron-containing lithium salt is one or more selected from lithium difluorooxalatoborate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium fluoroalkoxyborate, lithium fluoroalkoxyfluoroborate, lithium fluoroalkoxybisfluoroborate and lithium fluoroalkoxytrifluoroborate, preferably lithium difluorooxalatoborate; and / or The fluorinated amide compound is one or more selected from N,N-dimethyltrifluoroacetamide, N-methoxy-N-methyltrifluoroacetamide, N-methyltrifluoroacetamide, N,N-diethyltrifluoroacetamide, N-(trifluoromethanesulfonyl)trifluoroacetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, bis(trimethylsilyl)trifluoroacetamide, N-methyltrimethylsilyltrifluoroacetamide, N-methylbis(trifluoroacetyl)amide, trifluoroacetamide and bistrifluoroacetamide, preferably N,N-dimethyltrifluoroacetamide; Preferably, the electrolyte comprises lithium difluorooxalatoborate and N,N-dimethyltrifluoroacetamide, and the molar ratio of lithium difluorooxalatoborate to N,N-dimethyltrifluoroacetamide is 1:
5.
8. The negative electrode-free lithium metal battery according to claim 1, wherein: The separator is selected from porous polyolefin polymer films or porous non-woven fabrics. Furthermore, at least one side of the diaphragm has a ceramic coating or a solid electrolyte coating.
9. The method for preparing a negative electrode-free lithium metal battery according to any one of claims 1 to 8, comprising the following steps: Assembling a positive electrode, a negative electrode current collector, a separator and an electrolyte into a negative electrode-free lithium metal battery; The negative electrode-free lithium metal battery is charged at a constant current and / or a constant voltage after liquid injection and packaging and before formation. During the charging process, the nucleation overpotential of the metal lithium is controlled to be 0.1 to 2 V relative to the standard potential of the metal lithium, thereby obtaining the negative electrode-free lithium metal battery including the negative electrode current collector for forming a lithium planting layer; Preferably, the constant current charging process is: charging at a constant charging rate C1 at a temperature T1, and the charging time is t1; The constant voltage charging process is: at temperature T2, charging with a constant charging voltage V1 and a charging capacity of R1; Among them, C1 is 0.3 to 10.0C, preferably 0.5 to 5C, more preferably 0.8 to 3C, t1 is 0.1 to 3600 s, preferably 1 to 100 s, more preferably 10 to 60 s, T1 is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C, V1 is 3.2 to 6 V, preferably 3.8 to 5 V, more preferably 3.8 to 4.2 V, R1 is 0.01~1mAh / cm 2 , preferably 0.02 to 0.5 mAh / cm 2 , more preferably 0.02 to 0.2 mAh / cm 2 , T2 is -60 to 120°C, preferably -30 to 60°C, more preferably -30 to 30°C.
10. Use of the negative electrode-free lithium metal battery according to any one of claims 1 to 8 in electronic devices, smart grids or electric vehicles.
Citation Information
Cited By
Halide-doped carbon skeleton, preparation method thereof and application of halide-doped carbon skeleton in negative-electrode-free lithium metal battery
CN120841493A